2020
DOI: 10.1371/journal.pone.0239835
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multimorbidity in the Cypriot population; A cross-sectional study (2018–2019)

Abstract: Background Multimorbidity is defined as the co-existence of two or more chronic conditions. As life expectancy is increasing so does the prevalence of multimorbidity. Our aim was to estimate the prevalence of multimorbidity in Cyprus and identify the most prevalent diseases. Methods A representative sample of n = 1140 individuals over 18 years old was surveyed during 2018–2019. Demographic characteristics as well as the presence of chronic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…Future prevention programmes and practice guidelines in Cyprus and elsewhere should take into account the beneficial effects of Mediterranean diet on multi-morbidity. are presented elsewhere (22) . Participants would provide verbal consent before responding anonymously, to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future prevention programmes and practice guidelines in Cyprus and elsewhere should take into account the beneficial effects of Mediterranean diet on multi-morbidity. are presented elsewhere (22) . Participants would provide verbal consent before responding anonymously, to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate was 90 %, and the final study sample did not significantly differ from the general population in terms of region, age and gender (all P-values > 0•05). More details of the study are presented elsewhere (22) .…”
Section: Settingmentioning
confidence: 99%
“…It has been reported that lack of sleep affects the endocrine pathways (48) and is associated with several chronic diseases, including cardio-metabolic and neurodegenerative diseases (23,24). In fact, in our study, the most common combination of diseases among people with multimorbidity were diseases of the circulatory and endocrine systems (29). In addition, most of the people with multimorbidity who have an endocrine or circulatory disorder reported poor quality of sleep.…”
Section: Current Smokermentioning
confidence: 51%
“…The mean number of conditions was 1.07. The most prevalent chronic diseases were the diseases of the circulatory system, followed by the endocrine system and the digestive-excretory system, whereas the most common combinations among people with multimorbidity were diseases of the circulatory and endocrine systems (25%), followed by circulatory and digestive-excretory systems (20%), and circulatory and nervous systems (19%) (29).…”
Section: Multimorbiditymentioning
confidence: 99%
See 1 more Smart Citation